Analisis Keefisiensian Moda Transportasi Umum KRL Sebagai Transportasi Pelajar di Jakarta - Widodo, Muhammad Saddam (Peneliti.net, 2025)
This research aims to analyze the efficiency of the KRL (Electric Train) public transportation mode as a means of transportation for students in Jakarta. This research uses a quantitative approach with a total of 30 students as respondents who regularly use KRL as the main mode of transportation. Data was collected regarding factors that influence the efficiency of KRL use. The research results show that KRL is an efficient mode of transportation for students and is more affordable than other modes of transportation. Comfort and safety were also rated as good by the majority of respondents. However, several challenges such as passenger density during peak hours and schedule delays still need to be improved. This research concludes that KRL has great potential to become the main mode of transportation for students in Jakarta if several operational aspects can be improved. The proposed recommendations include increasing the number of carriages during peak hours, increasing travel frequency, and improving facilities at stations to increase user comfort and safety.